2016
DOI: 10.1007/978-3-319-25474-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Do Hearing Aids Improve Affect Perception?

Abstract: Normal-hearing listeners use acoustic cues in speech to interpret a speaker's emotional state. This study investigates the effect of hearing aids on the perception of the emotion dimensions arousal (aroused/calm) and valence (positive/ negative attitude) in older adults with hearing loss. More specifically, we investigate whether wearing a hearing aid improves the correlation between affect ratings and affect-related acoustic parameters. To that end, affect ratings by 23 hearing-aid users were compared for aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
0
14
1
1
Order By: Relevance
“…Picou 24 also assessed the perception of emotional valence and arousal in OHI listeners (N=13), but this time for nonspeech stimuli such as non-verbal human vocalizations (eg, laughter), animal vocalizations (eg, dog barking), and machine sounds (eg, dentist drill). In contrast to the findings of Schmidt et al, 23 the ratings given by the OHI listeners were significantly different from those of the YNH listeners, even when the OHI listeners were fitted with hearing instruments used for research purposes. The signal processing provided by the HAs neither improved nor impaired the perception of emotions in the OHI listeners.…”
Section: Introductioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Picou 24 also assessed the perception of emotional valence and arousal in OHI listeners (N=13), but this time for nonspeech stimuli such as non-verbal human vocalizations (eg, laughter), animal vocalizations (eg, dog barking), and machine sounds (eg, dentist drill). In contrast to the findings of Schmidt et al, 23 the ratings given by the OHI listeners were significantly different from those of the YNH listeners, even when the OHI listeners were fitted with hearing instruments used for research purposes. The signal processing provided by the HAs neither improved nor impaired the perception of emotions in the OHI listeners.…”
Section: Introductioncontrasting
confidence: 98%
“…So far, only a few studies investigated the auditory processing of voice emotions in speech in older-adult HI (OHI) persons when listening unaided and aided with HAs (for a recent overview, see Picou et al 22 ). Schmidt et al 23 assessed the emotional responses to speech sounds by asking OHI listeners (N=23), listening unaided or when wearing their own HAs, to rate short sentences in terms of valence (ie, their un/pleasantness) and arousal (ie, the level of activation produced). Those ratings were then compared to affect-related acoustic features (eg, the fundamental frequency, intensity) measured in the vocal stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…This finding in the present study is supported by Shi et al, 34 who found that adults using hearing aids were able to perceive the loudness of environmental sounds. Also, it was noted by Schmidt et al 35 that children using hearing aids could use the intensity cues to perceive emotions similar as normal-hearing listeners.…”
Section: Comparison Of Relative Loudness Judgment Between the Particimentioning
confidence: 99%
“…They compared 23 hearing impaired people with and without hearing aids with a control group (n=22). The affective perception, the emotional components, and the interpretation of excitation patterns could be improved with hearing aids [ 81 ].…”
Section: Necessity Of Early Hearing Rehabilitation and Hearing Aidmentioning
confidence: 99%